(untitled) (Editora Impacto Científico, 2025)
The article discusses the new paradigm of science, centered on systems thinking, and its implications for learning organizations. This paradigm breaks with the traditional fragmented and mechanistic view of science, proposing an integrated approach that recognizes the complexity, interdependence and uncertainty present in natural and social systems. This epistemological shift is fundamental to understanding the transformations in contemporary organizations, which face an increasingly dynamic and volatile environment. The key concepts of systems thinking are discussed, including the need to see organizations as living systems, in which the interactions between the elements are as important as the parts themselves. The importance of learning organizations is highlighted, which promote the creation, dissemination and continuous application of knowledge, adapting and innovating permanently. This capacity is vital for sustainability and competitiveness in a context of rapid technological and social evolution. The text also emphasizes the importance of cultural and mental change in organizations so that systemic thinking can be consolidated, highlighting the overcoming of obsolete paradigms and the valuing of skills such as personal mastery, shared vision and team learning. Digital transformation and the growing complexity of production systems demand integrative approaches that consider the multiple dimensions and implications of organizational processes. The article concludes that adopting the new scientific paradigm and systems thinking allows organizations to face contemporary challenges with greater resilience, promoting an environment of continuous learning, innovation and sustainable development. This change represents a step forward towards a more humane, integrated management system, aligned with the complexities of today’s world.